Activation of AdipoR1 with rCTRP9 Preserves BBB Integrity through the APPL1/AMPK/Nrf2 Signaling Pathway in ICH Mice. (8th December 2021) - Zhao, Wei; Kong, Fanping; Gong, Xiu; Guo, Zaiyu; Zhao, Lianhua; Wang, Sa
Abstract : Background . The disruption of the blood brain barrier (BBB) is the key factor leading to neurological impairment after intracerebral hemorrhage (ICH) injury. Adiponectin receptor 1 (AdipoR1) has an important effect contributing to the integrity of BBB. As a homologue of adiponectin, recombinant C1q/TNF-related protein 9 (rCTRP9) has neuroprotective effect in cerebrovascular diseases. The aim of this study was to investigate the protective effect of AdipoR1 activation with rCTRP9 on BBB integrity after ICH injury and the potential mechanisms. Methods . 177 male mice were subjected in this study. ICH was induced by injecting collagenase into the right basal ganglia. rCTRP9 was treated intranasally at 1 hour after ICH. Selective siRNA was administered prior to ICH. Western blot, immunofluorescence staining, neurobehavioral tests, and BBB permeability were evaluated. Results . ICH increased the expression of endogenous AdipoR1 and CTRP9. Administration of rCTRP9 ameliorated neurological deficits and reduced the BBB permeability at 24 hours in ICH mice. Furthermore, rCTRP9 promoted the expression of AdipoR1, APPL1, p-AMPK, Nrf2, and tight junctional proteins. The intervention of specific siRNA of AdipoR1, APPL1, and p-AMPK reversed the protective effects of rCTRP9. Conclusions . Activation of AdipoR1 with rCTRP9 improved neurological functions and preserved BBB integrity through the APPL1/AMPK/Nrf2 signaling pathway in ICH mice. Therefore, CTRP9 could serve as a promising therapeutic method to alleviate BBB injury following ICH in patients.